I've tried a lot of tricks but I'm still not able to solve the first order differential equation $$ xy'+y+x^4y^4e^x=0 $$

It's not an homogeneous or isobaric equation, it's not a simple linear equation and it's also not an exact equation.

For an exact differential equation I would need that: $$\frac{\partial x}{\partial x}=\frac{\partial(y+x^4y^4e^x)}{\partial y},$$ which is not the case.

Now I've also tried to find some sort of integrating factor $\lambda(x,y)$ to make the above equation exact. But this yielded another difficult equation:

$$ x\frac{\partial \lambda}{\partial x}+(y+x^4y^4e^x)\frac{\partial \lambda}{\partial y}+4\lambda x^4y^3e^x=0 $$

I don't know how to proceed to solve the above differential equation ? I'm thinking of substituting a series, but I'm afraid this would also complexify my problem :(. All tips (substitutions, ...) are appreciated !

  • 6
    $\begingroup$ Well, you do know that $[xy]' =xy'+y$. That might be a useful substitution. You get $u'+ u^4e^x=0$. $\endgroup$ – Arthur Oct 9 '14 at 7:39
  • 1
    $\begingroup$ Just to save you effort, it's not hamiltonian either. (Just checked) $\endgroup$ – Alan Oct 9 '14 at 7:50


Divide everything by $y^4$ and I suppose that the change of variable $\frac{1}{y^3}=z$ will become clear. The equation should become $$3 e^x x^4-x z'+3 z=0$$

I am sure that you can take from here.


You write: $xy'+y= - x^4 e^xy^4$. Consider two cases:

Case 1: $y=0$. It is easy to see that $y=0$ is a solution of the equation.

Case 2: $y\ne 0$. Dividing two both sides of the equation by $y^4$, we get $$x.y^{-4}y+y^{-3}=-x^4.e^x.$$ Put $z=y^{-3}$. Then $z'=-3y^{-4}y'$. So, $y^{-4}.y'=-\frac{1}{3}z$. Then we get $$-\frac{1}{3}xz'+z=-x^4e^x,$$ or $$xz'-3z=3x^4e^x,$$ or $$z'-\frac{3}{x}z=3x^3 e^x$$ Multiplying $\frac{1}{x^3}$ two sides of the latter equation, we get $$\frac{1}{{{x^3}}}z' - \frac{3}{{{x^4}}}z = 3{e^x},$$ or you can write in the form $$\frac{d}{{dx}}\left( {\frac{1}{{{x^3}}}.z} \right) = 3{e^x}.$$ This leads to $$\frac{1}{{{x^3}}}z = \int {3{e^x}dx} = 3{e^x} + C.$$ So, we get $z=3x^3e^x+Cx^3$. But $z=y^{-3}=\frac{1}{y^3}$, we deduce $$y = \frac{1}{{\sqrt[3]{z}}} = \frac{1}{{\sqrt[3]{{3{x^3}{e^x} + C{x^3}}}}}.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.